2018
DOI: 10.1093/cercor/bhy004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Regulation of Dendritic Spines Through NrCAM-Semaphorin3F Receptor Signaling in Developing Cortical Pyramidal Neurons

Abstract: Neuron-glial related cell adhesion molecule NrCAM is a newly identified negative regulator of spine density that genetically interacts with Semaphorin3F (Sema3F), and is implicated in autism spectrum disorders (ASD). To investigate a role for NrCAM in spine pruning during the critical adolescent period when networks are established, we generated novel conditional, inducible NrCAM mutant mice (Nex1Cre-ERT2: NrCAMflox/flox). We demonstrate that NrCAM functions cell autonomously during adolescence in pyramidal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(115 citation statements)
references
References 84 publications
(119 reference statements)
5
96
0
Order By: Relevance
“…While ADAM10 cKO mice have a reduced number of dendritic spines (Prox et al , ), NrCAM KO mice have increased dendritic spine densities. Together with Neuropilin‐2 and Plexin A3, NrCAM is part of a Sema3F receptor complex, which is mediating a Sema3F‐induced spine retraction (Demyanenko et al , ; Mohan et al , ). Thus, increased NrCAM surface levels, as we observed upon inhibition of ADAM10, would be expected to decrease spine density, as reported for ADAM10 cKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…While ADAM10 cKO mice have a reduced number of dendritic spines (Prox et al , ), NrCAM KO mice have increased dendritic spine densities. Together with Neuropilin‐2 and Plexin A3, NrCAM is part of a Sema3F receptor complex, which is mediating a Sema3F‐induced spine retraction (Demyanenko et al , ; Mohan et al , ). Thus, increased NrCAM surface levels, as we observed upon inhibition of ADAM10, would be expected to decrease spine density, as reported for ADAM10 cKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody does not react with other L1-CAMs in mouse brain or transfected HEK293 cells and does not bind nonspecifically to CHL1-null mutant mouse brain (Nikonenko et al, 2006). The NrCAM antibody, also directed against the extracellular region, does not cross-react with other L1-CAMs, as previously characterized (Demyanenko et al, 2011b(Demyanenko et al, , 2014Mohan et al, 2019). The Sema3B antibody was generated against a synthetic peptide (human Sema3B residues 100 -200 in the Sema domain) and reacts specifically with mouse or human Sema3B, not with Sema3F (Nguyen et al, 2011).…”
Section: Methodsmentioning
confidence: 56%
“…The ability of L1-CAMs and Sema3s to promote axon repulsion, taken together with their robust expression in the postnatal neocortex, suggested that they might also have a repellent function in cortical pyramidal neurons. Consistent with this hypothesis, Sema3F induces spine retraction in cortical pyramidal neurons (Tran et al, 2009), and NrCAM serves as a functional subunit of the Sema3F receptor complex to limit the density of spine subpopulations in the prefrontal cortex (PFC) and primary visual cortex (V1) (Tran et al, 2009;Demyanenko et al, 2014;Mohan et al, 2019).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations